Integration of Social Care Character Education for Grade 5 in Elementary Schools during the PPKM Period: Integrasi Pendidikan Karakter Peduli Sosial Kelas 5 Di Sekolah Dasar di Masa PPKM - Efendy, Eva Yulia; Amrullah, Muhlasin (Indonesian Journal of Education Methods Development, 2023)
This study aims to determine the Integration of Social Care Character Education for Class V at SD Muhammadiyah 8 Tulangan during the PPKM Period. The method used is a qualitative method. The research subjects were the principal, homeroom teacher of class V, and students of Class V at SD Muhammadiyah 8 Tulangan. Collecting data using observation, interviews and documentation. Checking the validity of the data using source triangulation and technical triangulation. The results of the study, namely strengthening social care character education in class V students, was applied through the method of habituation of students' social care activities on a regular basis. The supporting factors are full support from parents of students, commitment between teachers and guardians of students in monitoring social care activities of students in the school environment by participating in school programs, and adequate facilities that support the implementation of activities. While the inhibiting factors are technical and economic errors in the PPKM period.